Edaphic conditions of natural sites of Morchella and Phellorinia - Manikandan, K; Sharma, V P; Kumar, Satish; Kamal, Shwet; Shirur, Mahantesh (Mushroom Research, 2011)
Field surveys were conducted to study the edaphic conditions at the natural sites of Morchella and Phellorinia sp in parts of Himachal Pradesh and Rajasthan during 2010. Few clusters of Morchella were found from the field boundaries of maize in the Solan district of Himachal Pradesh during July. It was found under the microclimatic conditions of pear tree (Pyrus sp) in association with moist, fertile, clay loam soil. Phellorinia were collected from the sandy tract of Rajasthan during September. Phellorinia mushroom requires coarse, well-aerated sandy soil with poor nutrients. Both mushrooms requires specific but opposite edaphic conditions